Preparation and properties of antibacterial ABS plastics based on polymeric quaternary phosphonium salts antibacterial agents. (20th May 2019) - Zeng, Weizhen; He, Jingwei; Liu, Fang
Abstract : Antibacterial acrylonitrile‐butadiene‐styrene (ABS) plastics were prepared by adding polymeric quaternary phosphonium salts as antibacterial agents through a double screw extruder. The novel polymeric quaternary phosphonium salts (PBrMAP‐n) with alkyl chain length ranging from 3 to 11 were synthesized, and their chemical structures were confirmed by Nuclear magnetic resonance hydrogen spectroscopy ( 1 H‐NMR) and Fourier transform infrared spectroscopy (FT‐IR) spectra. The thermogravimetric analysis (TGA) results showed that all of the antibacterial agents had good thermal stability. The influence of addition amount as well as the alkyl chain length on mechanical properties and antibacterial properties was investigated. Compared with the pure ABS, all of PBrMAP‐n containing specimens had comparable tensile strength and flexural properties but reduced impact strength. Only samples with 10 wt% of PBrMAP‐11 exhibited more than 90% antibacterial efficiency against Escherichia coli and Staphylococcus aureus .